Building a competent health manager at district level: a grounded theory study from Eastern Uganda. Issue 1 (December 2016) - Tetui, Moses; Hurtig, Anna-Karin; Ekirpa-Kiracho, Elizabeth; Kiwanuka, Suzanne; Coe, Anna-Britt
Abstract Background Health systems in low-income countries are often characterized by poor health outcomes. While many reasons have been advanced to explain the persistently poor outcomes, management of the system has been found to play a key role. According to a WHO framework, the management of health systems is central to its ability to deliver needed health services. In this study, we examined how district managers in a rural setting in Uganda perceived existing approaches to strengthening management so as to provide a pragmatic and synergistic model for improving management capacity building. Methods Twenty-two interviews were conducted with district level administrative and political managers, district level health managers and health facility managers to understand their perceptions and definitions of management and capacity building. Kathy Charmaz's constructive approach to grounded theory informed the data analysis process. Results An interative, dynamic and complex model with three sub-process of building a competent health manager was developed. A competent manager was understood as one who knew his/her roles, was well informed and was empowered to execute management functions. Professionalizing health managers which was viewed as the foundation, the use of engaging learning approaches as the inside contents and having a supportive work environment the frame of the model were the sub-processes involved in the model. The sub-processes were interconnected although the respondents agreed that having a supportive work environment was more time and effort intensive relative to the other two sub-processes. Conclusions The model developed in our study makes four central contributions to enhance the WHO framework and the existing literature. First, it emphasizes management capacity building as an iterative, dynamic and complex process rather than a set of characteristics of competent managers. Second, our model suggests the need for professionalization of health managers at different levels of the health system. Third, our model underscores the benefits that could be accrued from the use of engaging learning approaches through prolonged and sustained processes that act in synergy. Lastly, our model postulates that different resource investments and a varied range of stakeholders could be required at each of the sub-processes.